2011
DOI: 10.1111/j.1479-828x.2011.01322.x
|View full text |Cite
|
Sign up to set email alerts
|

Lived experience of gestational diabetes mellitus among immigrant South Asian women in Australia

Abstract: South Asian women require culturally appropriate advice regarding strategies to reduce their risk of GDM as early as possible in pregnancy, ideally at the time pregnancy is confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
128
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(139 citation statements)
references
References 19 publications
9
128
2
Order By: Relevance
“…This study, in agreement with others [11,14,10,18], found that the overseas-bornwomen experienced additional barriers; lack of partner, family and social support resulting in isolation and stress, and diverse cultural preferences and expectations.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This study, in agreement with others [11,14,10,18], found that the overseas-bornwomen experienced additional barriers; lack of partner, family and social support resulting in isolation and stress, and diverse cultural preferences and expectations.…”
Section: Discussionsupporting
confidence: 79%
“…These studies reported barriers such as lack of assistance with childcare, mental distress, low partner and social support, resulting in poor compliance with the healthy lifestyle following childbirth [10,11,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was reassuring that those prescribed insulin reported feeling better on the regime, Bandyopadhyay et al (2011) reported similar findings. This cycle of emotions identifies an area of education which needs to be strengthened.…”
Section: Interpretation Of Findingsmentioning
confidence: 81%
“…13 Both techniques are well-accepted methods of qualitative research and have been used in studies regarding numerous disease states, including diabetes mellitus. [15][16][17][18][19][20] Interpretative phenomenology is an assessment technique used to gather qualitative data, 12 while thematic analysis is a technique used to analyze data obtained through qualitative research. [21][22][23] In thematic analysis, the researcher identifies patterns and themes in a subject's life and/or behavior, 14 which, in this study, consisted of a retrospective detailed investigation of participants' reflective writing about their active-learning diabetes simulation experience.…”
Section: Evauation and Assessmentmentioning
confidence: 99%